Biochemical changes associated with electron beam irradiation of rice and links to kernel discoloration during storage. Issue 5 (19th June 2019) - Mohammadi Shad, Zeinab; Steen, Emiel; Devlieghere, Frank; Mauromoustakos, Andy; Atungulu, Griffiths G.
Abstract: Background and objectives: Rice kernel discoloration during storage results in significant economic losses to rice growers and processors. This study aimed to elucidate the extent of chemical changes and microbial involvement on discoloration of rice kernels during storage. To segregate and/or diminish the effects of microbes, one lot of hybrid long‐grain rice (XL753) samples was irradiated with nonthermal electron beam (EB) dose of 14 kGy. The irradiated and nonirradiated control samples of rice at a moisture content (MC) of 21% on a wet basis were stored at three temperatures (20, 30, and 40°C) for 8 weeks. Samples were taken every 2 weeks for microbial and chemical analyses. Findings: A negative relationship was noted between discoloration and microbial load. The trend of increasing discoloration and chemical properties such as free sugars, free fatty acid, and free 5‐hydroxymethyl‐2‐furaldehyde (HMF), especially at higher storage temperatures and durations, suggested that biochemical changes were major drivers of the observed rice discoloration. The higher HMF in highly discolored rice (≥20%) explained nonenzymatic browning in the rice matrix during storage. Conclusions: From this study, it was drawn that the rice kernel discoloration was not directly related to the microbial load; the discoloration was seen in EBI rice even with 99% reduction in microbial load. However, it was clarified that the rice discoloration especially in EBI rice samples was related to the observed chemical changes, which were also storage temperature dependent. Significance and novelty: Milled rice discoloration during storage of rough rice is insufficiently understood. There is no information correlating changes in chemical attributes and microbial activity to discoloration of contemporary hybrid rice during storage. Therefore, the results of the current study provide important fundamental information and also suggest storage conditions required to arrest discoloration and maintain quality of contemporary milled hybrid rice.